2009
DOI: 10.1186/1472-6785-9-11
|View full text |Cite
|
Sign up to set email alerts
|

Within-host competitive exclusion among species of the anther smut pathogen

Abstract: Background: Host individuals represent an arena in which pathogens compete for resources and transmission opportunities, with major implications for the evolution of virulence and the structure of populations. Studies to date have focused on competitive interactions within pathogen species, and the level of antagonism tends to increase with the genetic distance between competitors. Anther-smut fungi, in the genus Microbotryum, have emerged as a tractable model for within-host competition. Here, using two patho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(38 citation statements)
references
References 54 publications
(86 reference statements)
2
35
0
Order By: Relevance
“…We provide evidence here that annual species become diseased at a significantly higher rate than perennial species under artificial inoculation. As verification of the artificial inoculation protocol used here, we find that infection rates on perennial species are comparable to those measured in prior studies using similar techniques (Biere and Honders 1996; Antonovics et al 2002; Hood 2003; Gold et al 2009). Moreover, the variation in infection rates observed between species is unlikely to be a technical artifact, as previous greenhouse and field experiments have shown that it represents heritable variation in physiological resistance (Alexander et al 1993; Biere and Honders 1996).…”
Section: Discussionsupporting
confidence: 86%
“…We provide evidence here that annual species become diseased at a significantly higher rate than perennial species under artificial inoculation. As verification of the artificial inoculation protocol used here, we find that infection rates on perennial species are comparable to those measured in prior studies using similar techniques (Biere and Honders 1996; Antonovics et al 2002; Hood 2003; Gold et al 2009). Moreover, the variation in infection rates observed between species is unlikely to be a technical artifact, as previous greenhouse and field experiments have shown that it represents heritable variation in physiological resistance (Alexander et al 1993; Biere and Honders 1996).…”
Section: Discussionsupporting
confidence: 86%
“…As with many diseases, the anther‐smut life history plays a role in shaping where the pathogen is found in nature. Anther‐smut fungi in the genus Microbotryum are obligate, biotrophic pathogens of perennial plants mainly in the Caryophyllaceae (Hood et al, ; Thrall, Biere, & Antonovics, ), where infections cause host sterility, are systemic and persistent, and have the potential to competitively exclude subsequent invasion by other Microbotryum pathogens (Gold et al, ; Hood, ; López‐Villavicencio et al, ). There are many host species for anther smut with broad and overlapping geographic distributions (Hitchcock & Maguire, ; Hood et al, ), and disease incidence can be remarkably high in some host species.…”
Section: Methodsmentioning
confidence: 99%
“…Anther‐smut disease, caused by fungi in the genus Microbotryum , is one of the most studied host–pathogen associations in natural systems (Figure ). This disease has been used as a model for pathogen speciation, pollinator‐mediated dispersal, multiple infection, biological invasion, and competition (Abbate & Antonovics, ; Bruns, Antonovics, & Hood, ; Fontaine, Gladieux, Hood, & Giraud, ; Giraud, Gladieux, & Gavrilets, ; Gold, Giraud, & Hood, ; Kemler et al, ; Le Gac, Hood, Fournier, & Giraud, ; Vercken et al, ). Research has shown that the fungi formerly grouped under the Microbotryum violaceum epithet represent a large species complex, consisting of many independent lineages, each specific (i.e., endemic) to only one or a very small number of host species (Kemler et al, ; Le Gac et al, ; Lutz et al, ; Piątek, Lutz, & Kemler, ; de Vienne, Hood, & Giraud, ).…”
Section: Introductionmentioning
confidence: 99%
“…DNA was extracted, using the Chelex (Bio‐Rad) method (Bucheli et al 2001), from one to two anthers from a single flower derived from each diseased sample. Artificial inoculation at the single meristem stage of seedlings largely prevents coexistence of multiple infections, resulting in systemic infection by the single pathogen genotype that persists in subsequently derived meristems (Hood 2003; Gold et al 2009). Anthers from a single flower were therefore considered accurate for genetic typing of an infection under our inoculation protocol.…”
Section: Methodsmentioning
confidence: 99%
“…Anthers from a single flower were therefore considered accurate for genetic typing of an infection under our inoculation protocol. Even in the unlikely event of multiple infections, they would segregate in different stems (Hood 2003; Gold et al 2009; López‐Villavicencio et al 2011), and our genotyped strains would represent an unbiased sample of the infecting strains.…”
Section: Methodsmentioning
confidence: 99%